Comparison of Shockwave Lithotripsy and Microperc for Treatment of Kidney Stones in Children - Hatipoglu, Namik Kemal; Sancaktutar, Ahmet Ali; Tepeler, Abdulkadir; Bodakci, Mehmet Nuri; PENBEGÜL, NECMETTİN; Atar, Murat; BOZKURT, YAŞAR; Soylemez, Haluk; Silay, Mesrur Selcuk; Istanbulluoglu, Mustafa Okan; Akman, Tolga; Armagan, Abdullah (My University, 2013)
Purpose: We aimed to compare the outcomes of microperc and shockwave lithotripsy (SWL) for treatment of kidney stones in children. Patients and Methods: The medical records of 145 patients under the age of 15 years with opaque and single kidney stones treated with either SWL or microperc were retrospectively reviewed. Both groups were compared in terms of fluoroscopy and operative time, re-treatment, complications, success rate, and secondary and total number of procedures. Results: Microperc and SWL were performed on 37 and 108 pediatric patients, respectively. The mean age of the patients was 5.914.03 years (1-15) and 8.43 +/- 4.84 (1-15) years in the SWL and microperc groups, respectively (P=0.004). The mean stone size was 11.32 +/- 2.84 (5-20) mm in the SWL group and 14.78 +/- 5.39 (6-32) mm in the microperc group (P<0.001). In the SWL group, 31 (28.7%) patients underwent a second SWL session and 6 (5%) had a third session. Finally, 95 (88%) patients were stone free at the end of the SWL sessions. In the microperc group, the stone-free rate was 89.2% in a single session (P=0.645). The mean duration of hospitalization was 49.2 +/- 12.3 (16-64) hours in the microperc group and 8.4 +/- 2.3 (6-10) hours per one session in the SWL group (P<0.001). The fluoroscopy time was significantly longer in the microperc group compared with the SWL group (147.3 +/- 95.3 seconds vs 59.6 +/- 25.9 seconds, P<0.001). The rate of requirement for an auxiliary procedure was higher in the SWL group than in the microperc group. The overall complication rates for the microperc and SWL groups were 21.6% and 16.7%, respectively (P=0.498). Conclusions: The results of our study demonstrate that microperc provides a similar stone-free rate and a lower additional treatment rate compared with SWL in the treatment of kidney stone disease in children.